Формулы сокращённого умножения (представьте в виде произведения многочленов) 36(b-1)^2-25b^2 -(x-3b)^3-(x+3b)^3

Холзи14 Холзи14    2   03.09.2019 15:30    0

Ответы
вика45890 вика45890  06.10.2020 15:04
Разность квадратов:
36(b-1)^2-25b^2=(6(b-1)-5b)(6(b-1)+5b)=(6b-6-5b)(6b-6+5b)=(b-6)(11b-6).

Сумма кубов: a^3+b^3=(a+b)(a^2-ab+b^2)

-{(x-3b)^3+(x+3b)^3}=-(x-3b+x+3b)((x-3b)^2-(x-3b)(x+3b)+(x+3b)^2)=

-2x(x^2-6xb+9b^2-(x^2-9b^2)+x^2+6xb+9b^2)=

-2x(2x^2+18b^2-x^2+9b^2)=-2x(x^2+27b^2).
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра